2019
DOI: 10.1002/eji.201848073
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific production of MicroRNA‐155 inhibits melanocortin 5 receptor‐dependent suppressor macrophages to promote experimental autoimmune uveitis

Abstract: Tissue-specific immune regulation is an important component of the immune response relevant to many areas of immunology. The focus of this study is on tissue-specific mechanisms that contribute to autoimmune uveitis. Precise gene regulation is necessary for the proper expression of an inflammatory or regulatory response. This precision gene regulation can be accomplished by microRNA at the level of the mRNA transcript. miR-155, in particular, has a complicated role in the immune response with positive and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Aberrant miRs expression has been reported in uveitis ( Kaneko et al., 2012 ; Muhammad et al., 2019 ; Puccetti et al., 2018 ; Wei et al., 2019 ). However, the molecular basis for miR dysregulation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant miRs expression has been reported in uveitis ( Kaneko et al., 2012 ; Muhammad et al., 2019 ; Puccetti et al., 2018 ; Wei et al., 2019 ). However, the molecular basis for miR dysregulation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…miR-30b-5p is downregulated in the spleen, lymph nodes, and eye tissues of rats with autoimmune uveitis, and both in vitro and in vitro experiments have confirmed that supplementation with miR-30b-5p can reduce the level of IL-10 and TLR4-positive cells, thereby having a certain inhibitory effect on uveitis [ 95 ]. Meanwhile, miR-155 has been shown to promote M1 macrophage polarization and thus exert proinflammatory effects, showing remission to EAU after reducing miR-155 expression levels [ 67 , 96 ]. However, how miR-155 regulates the polarization of macrophages by regulating the expression of target genes and then affects the pathogenesis of uveitis needs to be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…10 Many miRNAs regulate up to hundreds of mRNAs, while their expression is tissuespecific. 11 Thus, due to their significant biological role as regulators of gene expression, miRNAs play an essential role both in physiological and pathophysiological processes. 12 MiRNAs carry unique properties such as their remarkable stability in plasma, their resistance to harsh conditions like boiling, low and high pH, RNases, long storage conditions as well as their withstanding of repetitive freezing and thawing cycles.…”
Section: Circulating Mirnasmentioning
confidence: 99%
“…MiRNAs are short (~22 nucleotides in length) single‐stranded RNAs, that have been implicated in the regulation of gene expression by binding to target mRNAs in eukaryotic cells 9 modulating in this way various cellular functions including cell growth, proliferation, differentiation, and apoptosis 10 . Many miRNAs regulate up to hundreds of mRNAs, while their expression is tissue‐specific 11 . Thus, due to their significant biological role as regulators of gene expression, miRNAs play an essential role both in physiological and pathophysiological processes 12 …”
Section: Circulating Mirnasmentioning
confidence: 99%